Methods and recent advances in speciation analysis of mercury chemical species in environmental samples: a review. Issue 1 (1st October 2016) - Amde, Meseret; Yin, Yongguang; Zhang, Dan; Liu, Jingfu
Abstract: Mercury (Hg) and its compounds are much concerned for their high toxicity and wide presence in the environment. Since the toxicity of Hg is species dependent, various methods have been developed for the speciation analysis of Hg. This review focus on the determination and speciation analysis of Hg chemical species in water, sediment, and soil samples. Recent developments on sample pre-treatment and extraction/pre-concentration, separation, and quantification of Hg chemical species, and associated analytical challenges have been reviewed and briefly discussed based on recent reports.